Road Embankment Using EPS - Geofoam - Rosamalina Yusop (School of Environmental Engineering, Universiti Malaysia Perlis, 2016)
The objectives of this project are to study the effect of groundwater level for road embankment treated by EPS-Geofoam through the computer simulation.To analysis the effect of slope gradient for road embankment treated by EPS-Geofoam using the Finite Element Method (FEM) and Limit Equilibrium Method (LEM).